The Colonial Bastille : a History of Imprisonment in Vietnam, 1862-1940. - Zinoman, Peter (University of California Press, 2001)
Peter Zinoman's original and insightful study focuses on the colonial prison system in French Indochina and its role in fostering modern political consciousness among the Vietnamese. Using prison memoirs, newspaper articles, and extensive archival records, Zinoman presents a wealth of significant new information to document how colonial prisons, rather than quelling political dissent and maintaining order, instead became institutions that promoted nationalism and revolutionary education.